Do biological disease-modifying antirheumatic drugs reduce the spinal fracture risk related to ankylosing spondylitis? A longitudinal multiregistry matched cohort study. Issue 12 (28th December 2017) - Robinson, Yohan; Olerud, Claes; Willander, Johan
Abstract : Objectives: Ankylosing spondylitis (AS) is associated with an increased spinal fracture risk due to the loss of elasticity in spinal motion segments. With the introduction of biological disease-modifying antirheumatic drug (bDMARD) treatment for AS, the individual course of the disease has been ameliorated. This study aims to examine the association of bDMARD treatment and risk of spinal fracture. Design: Longitudinal population-based multiregistry observational matched cohort study. Setting: Swedish Patient Registry 1987–2014 and Swedish Prescribed Drugs Registry 2005–2014. Participants: Included were patients ≥18 years of age receiving treatment at a healthcare facility for the primary diagnosis of AS. About 1352 patients received more than one prescription of bDMARD from 2005 to 2014. An untreated control group was created by propensity score matching for age, sex, comorbidity, antirheumatic prescriptions and years with AS (n=1352). Main outcome measures: Spinal fracture-free survival. Results: No bDMARD treatment-related effect on spinal fracture-free survival was observed in the matched cohorts. Male gender (HR=2.54, 95% CI 1.48 to 4.36) and Charlson Comorbidity Index score (HR=3.02, 95% CI 1.59 to 5.75) contributed significantly to spinal fracture risk. Conclusion: bDMARD had no medium-term effect on the spinal fracture-free survival in patients with AS. Trial registration number: NCT02840695; Post-results .